Challenges in Implementing Quality Education at INTI International University: An Examination of Human Resource Management Practices - Ramachandaran, Sharmila Devi; Nuraini, Riska; Kaur, Sukhmeet (Journal of Ecohumanism, 2024)
This study investigates the challenges that INTI International University has had in integrating Sustainable Development Goal (SDG) 4 by ensuring inclusive, high-quality education and opportunities for lifelong learning into its HRM practices. Key problems identified by the study include the need to accommodate varied faculty requirements in an inclusive environment, integrate new technologies with current teaching approaches, and attract and retain talented instructors. The implementation of HRM strategies is hampered by resource constraints, changing educational requirements, and the need for ongoing strategy modification, according to the insights of an HR specialist. The results emphasize the necessity of continual modifications to HRM practices to address these issues and forward the objective of universal access to high-quality education.